2014
DOI: 10.1002/art.38662
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Abnormal Epidermal Nerve Fiber Density in Fibromyalgia: Clinical and Immunologic Implications

Abstract: Objective. A subset of patients with fibromyalgia (FM) exhibit a large fiber demyelinating peripheral polyneuropathy akin to that seen in chronic inflammatory demyelinating polyneuropathy (CIDP). It has been suggested that this demyelinating process is likely to be immune mediated. Because it is known that similar large fiber neuropathic lesions may be associated with a cutaneous small fiber neuropathy, we sought to determine the prevalence of small fiber neuropathy, as measured by epidermal nerve fiber densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 39 publications
2
73
0
3
Order By: Relevance
“…Further, they support the concept of a connection between FM and CIDP, at least in a subgroup of these patients. As the immune system is known to be instrumental in the genesis of CIDP, we reason that a subgroup of FM is likely to have a significant immune mediated element to its pathogenesis as well (7,9,30). Finally, we believe that our findings may be of considerable interest to students of FM, to those investigating the origin of immune mediated neuropathic pain, and to clinicians who deal with FM on a daily basis.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Further, they support the concept of a connection between FM and CIDP, at least in a subgroup of these patients. As the immune system is known to be instrumental in the genesis of CIDP, we reason that a subgroup of FM is likely to have a significant immune mediated element to its pathogenesis as well (7,9,30). Finally, we believe that our findings may be of considerable interest to students of FM, to those investigating the origin of immune mediated neuropathic pain, and to clinicians who deal with FM on a daily basis.…”
Section: Discussionmentioning
confidence: 71%
“…The laboratory and clinical screening of our FM participants paralleled that used by us previously (9). Only records from those subjects who lacked evidence of any disorder known to be associated with LFN were included in our final FM study cohort.…”
Section: Clinical Assessments and Demographicsmentioning
confidence: 99%
“…The results demonstrated that ENFD was reduced in a subset of patients with FMS [463][464][465][466][467]. Several other findings in these patients were consistent with a small fiber polyneuropathy, including elevated scores on neuropathic pain questionnaires [464,535], a high frequency of paresthesias [466], stocking hypesthesia [465], and some abnormal results of sensory testing [463,467], and autonomic function testing [464]. More specifically, Üceyler et al [463] provided evidence of deficits in Aδ and C fiber function in the overall cohort of patients they investigated.…”
Section: Further Potential Peripheral Nociceptive Inputmentioning
confidence: 92%
“…In view of the growing evidence that FMS is associated with signs and symptoms of small-fiber neuropathy in a substantial subset of patients [463][464][465][466][467], the SCN9 gene is of particular interest since 8/28 (29 %) of patients who met stringent criteria for idiopathic small fiber neuropathy were demonstrated to harbor seven different gain of function mutations in this gene [468]. The SCN9 gene encodes the sodium channel Nav1.7 and has been the target of intense research since the discovery that loss of function mutations result in complete insensitivity to pain, whereas gain of function mutations cause severe chronic pain conditions like inherited erythromelalgia and paroxysmal extreme pain disorder.…”
Section: Potential Pathogenetic Mechanisms Genetics and Epigeneticsmentioning
confidence: 99%
“…Distal leg SB with quantification of intradermal small fibers density using established rules is considered an effective technique for the diagnosis of small fibers neuropathy 29,30 . With SB it was possible to detect evidences of small fibers neuropathy in a variety of conditions 31 , including fibromyalgia patients 32,33 . So, SB has been recommended as important part of diagnostic tests for small fibers neuropathy in fibromyalgia patients 34 .…”
Section: Skin Biopsymentioning
confidence: 99%